2018
DOI: 10.4314/as.v16i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of inorganic fertilizer and spacing on growth and yield of two maize cultivars under <i>Striga hermonthica</i> infestation

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Therefore, it is essential to determine the optimal combination of maize varieties and Nfertilizer application rates that will result improved yields in different agroecologies. Several studies have shown significant responses of maize varieties to N-fertilizers (Kamara et al, 2009;Garba et al, 2017;Ewansiha et al, 2020). However, a study by Ewansiha et al (2019) reported that late maturing maize varieties had higher grain yield than early maturing maize varieties in the rainforest agroecology of Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is essential to determine the optimal combination of maize varieties and Nfertilizer application rates that will result improved yields in different agroecologies. Several studies have shown significant responses of maize varieties to N-fertilizers (Kamara et al, 2009;Garba et al, 2017;Ewansiha et al, 2020). However, a study by Ewansiha et al (2019) reported that late maturing maize varieties had higher grain yield than early maturing maize varieties in the rainforest agroecology of Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…These researchers stated that tolerant maize hybrids and open-pollinated cultivars have been developed with moderate levels of resistance and reduced numbers of emerging Striga plants. Moreover, from an experimental research conducted in the Southern Guinea Savannah, it was reported that a resistance maize variety performed remarkably better than the local variety under Striga infested fields (Garba, Yakubu, Gwandu, & Muhammad, 2014).…”
Section: Introductionmentioning
confidence: 99%